E-peptides control bioavailability of IGF-1. - Marianne Smedegaard Hede; Ekaterina Salimova; Agnieszka Piszczek; Emarald Perlas; Nadine Winn; Tommaso Nastasi; Nadia Rosenthal (PLoS ONE, 2012)
Insulin-like growth factor 1 (IGF-1) is a potent cytoprotective growth factor that has attracted considerable attention as a promising therapeutic agent. Transgenic over-expression of IGF-1 propeptides facilitates protection and repair in a broad range of tissues, although transgenic mice over-expressing IGF-1 propeptides display little or no increase in IGF-1 serum levels, even with high levels of transgene expression. IGF-1 propeptides are encoded by multiple alternatively spliced transcripts including C-terminal extension (E) peptides, which are highly positively charged. In the present study, we use decellularized mouse tissue to show that the E-peptides facilitate in vitro binding of murine IGF-1 to the extracellular matrix (ECM) with varying affinities. This property is independent of IGF-1, since proteins consisting of the E-peptides fused to relaxin, a related member of the insulin superfamily, bound equally avidly to decellularized ECM. Thus, the E-peptides control IGF-1 bioavailability by preventing systemic circulation, offering a potentially powerful way to tether IGF-1 and other therapeutic proteins to the site of synthesis and/or administration.